Preferable effects of olmesartan/calcium channel blocker to olmesartan/diuretic on blood pressure variability in very elderly hypertension. Issue 10 (October 2015) - Rakugi, Hiromi; Ogihara, Toshio; Saruta, Takao; Kawai, Tatsuo; Saito, Ikuo; Teramukai, Satoshi; Shimada, Kazuyuki; Katayama, Shigehiro; Higaki, Jitsuo; Odawara, Masato; Tanahashi, Norio; Kimura, Genjiroh
<x xml:space="preserve">Abstract</x> Objective: The aims of this subanalysis of the COLM trial [NCT00454662] were to compare visit-to-visit variability (VVV) of blood pressure (BP) between age groups and between two treatment combinations, that is, the angiotensin II receptor blocker, olmesartan combined with a calcium channel blocker (CCB), or a diuretic and to investigate the effect of VVV of BP on cardiovascular events in elderly hypertensive patients. Methods: Hypertensive patients ages 65–84 years with a history of and/or risk factors for cardiovascular disease were randomized to receive treatment with olmesartan along with either a CCB or a diuretic for at least 3 years. This subanalysis comprised 4876 patients who had their office BP measured at least three occasions (median nine occasions) during the follow-up period. VVV of BP was defined by several metrics including the within-individual standard deviation of every visit during the follow-up period. Results: VVV of SBP was larger in the very elderly group (75–84 years) than in the elderly group (65–74 years). VVV of SBP was smaller in the olmesartan along with CCB group than in the olmesartan along with diuretic group, especially in very elderly patients and also isolated systolic hypertensive patients. The incidence rate of primary endpoint increased along with an increment in the SD of SBP in all of the age and treatment groups. Conclusion: VVV of SBP may mediate the preferable effect of combination of angiotensin II receptor blocker along with CCB on cardiovascular events in the very elderly and also isolated systolic hypertensive patients.